Production and properties of agar from the invasive marine alga, Gracilia Vermiculophylla (Gracilariales, Rhodophyta) - Villanueva, R. D. (2010)
The utilization potential, in terms of agar production, of the invasive alga, Gracilaria vermiculophylla, collected at Ria de Aveiro, northwestern Portugal was investigated. The agar yield ranged from 15% to 33%, with pre-extraction treatment with alkali generally increasing the yield. The gel quality (gel strength and apparent Young’s modulus) was best (>600 g cm−2 and >1,000 kPa, respectively) when alkali treatment with 6% NaOH for 3.5 h was performed. At these pretreatment conditions, the effect of extraction time was also investigated and highest yield and best gel quality were obtained with a 2 h extraction time. By employing these extraction conditions, G. vermiculophylla can be a source of industrial food-grade agar. The structure of agar from G. vermiculophylla was determined through chemical techniques and FTIR and NMR spectrometry. It is mainly composed of alternating 3-linked D-galactose and 4-linked 3,6-anhydro-L-galactose, with methyl substitution occurring at 16–19 mol% of C-6 in 3-linked units and 2–3 mol% of C-2 in 4-linked units. A minor sulfation on C-4 of 3-linked units was also detected; while precursor units (6-sulfated 4-linked galactosyl moieties) were found in the native extract.